Signifikansi Teladan Musa Dan Aplikasi Bagi Pemimpin Organisasi - Rezeki Putra Gulo (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The example of Moses' leadership has become a reflection of contemporary Christian leadership, especially for organizational leadership. Today, some organizational leaderships are trapped in unhealthy leadership which results in unwanted events, one example being corruption, running away from calls, being less responsible, and being more concerned with personal needs. Avoiding events like this, today's organizational leadership wants to have complete self-integrity, missionary, obedient to God, responsible, loyal, and prioritizes the needs of others in leading the organization. The method used by the author in writing this article is a qualitative method, namely by literature research (approach). The conclusion from the author about the significance of Moses' example and implementation for today's organizational leadership is that Moses' example is indispensable for today's organizational leadership in carrying out their duties and responsibilities as leaders and servants of God's sheep.